A Phenomenology of Vocational Teacher Experience to Create Independence Students Disabilities - Rachmawati, Eka; Pardjono; Sudira, Putu; Mufidah, Lina (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the opinions and experiences of teachers working in special schools. Especially vocational skills teachers and teachers who receive vocational training. Teacher education background needs to be considered. The research method uses a qualitative phenomenological approach. The semi-structured interview form was prepared in the preliminary research. Close and in-depth interviews to find out the experience of teachers dealing with special students. An easily accessible purposive sampling method is used to determine participants. Interviews were conducted with 10 selected teachers in 5 districts. Data obtained from opinions were analyzed descriptively. Preliminary findings indicate that teachers are the main key to learning in schools. The teacher provides vocational skills as an activity that supports the development of children’s independence. Demonstration of skills by playing shows that they find a desire to learn vocational cooking skills Student independence is obtained slowly, repeatedly, and patiently. The material provided must be easy and concise. Security is the main thing. Student independence is formed by students, teachers and parents. Keywords: Phenomenology, Teacher’s Opinion, Vocational, Independence, Disabilities The purpose of this study is to examine the opinions and experiences of teachers working in special schools. Especially vocational skills teachers and teachers who receive vocational training. Teacher education background needs to be considered. The research method uses a qualitative phenomenological approach. The semi-structured interview form was prepared in the preliminary research. Close and in-depth interviews to find out the experience of teachers dealing with special students. An easily accessible purposive sampling method is used to determine participants. Interviews were conducted with 10 selected teachers in 5 districts. Data obtained from opinions were analyzed descriptively. Preliminary findings indicate that teachers are the main key to learning in schools. The teacher provides vocational skills as an activity that supports the development of children’s independence. Demonstration of skills by playing shows that they find a desire to learn vocational cooking skills Student independence is obtained slowly, repeatedly, and patiently. The material provided must be easy and concise. Security is the main thing. Student independence is formed by students, teachers and parents.